Model Test of the Pullout Bearing Capacity of End-Bearing Torpedo Anchors - Gang Li; Jinli Zhang; Jia Liu (Journal of Marine Science and Engineering, 2022)
Torpedo anchors (TAs) are regarded as one of the most efficient mooring solutions for taut mooring systems, and end-bearing TAs are a new type of TA that primarily relies on end-bearing plates at the tail to generate a pile-end resistance to improve their pulloutbearing capacity (P). Therefore, the estimation of the pullout capacity of the end-bearing TA is vital for the design of offshore floating facilities. In this study, pullout model tests were conducted to investigate the P of conventional and end-bearing TAs and examine the effects of factors such as the embedment depth (h), the relative density (Dr), the pullout angle (α), and the area (A) of the bearing plates on P. The test results show that, under oblique pullout loading, the P on the conventional TA increased slowly as displacement increased, while there was a peak on the load–displacement curve of each end-bearing TA with a relatively large A. The end-bearing TAs considerably outperformed the conventional TAs in terms of the P. In addition, increasing h, Dr, and A significantly increased the P of the end-bearing TAs. However, increasing h and Dr slightly decreased the ability of the bearing plates to increase the P of the end-bearing TAs. These research results can provide a guideline for TA installation in deep-sea engineering.